Introducing a Local Fee: Exploring Tourists' Preferences for Beach Improvements in Terengganu, Malaysia - Kamaludin, Mahirah; Mat Alipiah, Roseliza; Samdin, Zaiton; Koris, Roshanim (Journal of Regional and City Planning, 2025)
Tourists are naturally attracted to picturesque landscapes, clean water, and aesthetically pleasing environments. Beach improvements and well-maintained beaches are vital for attracting tourists and boosting the tourism sector. This study investigates tourists' preferences and their Willingness to Pay (WTP) for beach improvements at Miami Beach, Terengganu, Malaysia, using a face-to-face survey of 277 tourists. The study examines four beach attributes (cleanliness, facilities, aesthetics, and local fees) through a Choice Experiment (CE) method. Findings reveal that tourists place the highest Marginal WTP (MWTP) value on the "facilities Level 3" attribute, with a calculated WTP of MYR14.179 (USD2.97). The results indicate that tourists value improved facilities the most, followed by cleanliness, and aesthetics, highlighting their strong preference for improved infrastructure. These insights are crucial for policymakers and governments to prioritize resource allocation and formulate policies that align with public values, thereby promoting sustainable tourism development. The study underscores the potential of introducing a local fee to fund these improvements, supporting economic growth, environmental sustainability, and community well-being, in alignment with multiple UN Sustainable Development Goals (SDGs).